Analisis Knowledge, Skills, Attitude Lulusan Akuntansi di Era Industri 4.0 - Alya Shofa Deaz; Sugeng Riadi (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
This study aims to determine the knowledge, skills, attitude (KSA) that accounting graduates must possess in the industrial era 4.0 in order to remain relevant along with technological developments based on the perspectives of regulators, academics and graduate users. This type of research is qualitative research. In this study, researchers used primary data obtained from interviews with informants. The informants in this study were the Chairman of the Indonesian Institute of Accountants (IAI) in the Riau Islands region, the Head of the Batam State Polytechnic Managerial Accounting Study Program, and the HRD of companies in Batam. Based on the perspective of the regulator, students must have internship experience, actively participate in seminars, problem solving skills and good attitude. The academic perspective emphasizes academic scores (GPA), being able to adapt, thinking critically, leadership and having fighting power. The perspective of graduate users is to have digital analysis, computer skills and creative skills. In addition, the three perspectives also have the same view that accounting graduates must be technologically literate, have basic knowledge of accounting, analytical skills, communication skills, have work experience, foreign language skills, professional certification, initiative, teamwork, integrity, meticulous and detailed, discipline, responsibility and respect for others are very important.